Quality of internal audit function : progressing towards quantitative measurement scales / Mohd Ariff Kasim ... [et al.] - Kasim, Mohd Ariff; Mohd Hanafi, Siti Rosmaini; Abdul Aziz, Asmah; Kasim, Isahak (Faculty of Business Management, 2012)
The primary objective of this study is to construct a valid and reliable instrument to quantitatively measure the quality of internal audit function via the level of conformance by internal auditors towards the International Professional Practice Framework (IPPF). This study involves development of an instrument to quantitatively measure quality of internal audit functions. Two separate pilot tests were performed. The instrument was also reviewed by two experts in internal auditing from the USA and Malaysia. The final data were collected from 400 internal auditors, auditors, accountant and account executives in Malaysia. The present study concludes that most of the existing instruments measuring internal audit quality suffer major weaknesses that limit its value and usability for empirical studies. The results indicated that the new instrument satisfies the criteria for a valid and reliable research instrument and conform to the existing framework suggested by the IIA. The instrument could serve as additional assessment tools for audit committee in assessing the quality of internal audit in line with the new Bursa Malaysia Listing Requirements. This present study hopes to enhance the literature by suggesting an instrument that could initiate more empirical research in internal auditing. A new approach of measurement was used as a solution to existing instruments that were limited to the use of categorical, Likert-based measurement scales. This present study suggests a modified measurement scales that allow collection or ratio data. Moreover, this instrument also enables more advance statistical analysis to be conducted.